Wire for water treatment filters
Patent Information
- Application Number
- JP2020204612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-09
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-12-09
AI Technical Summary
【0007】 本発明によれば、水処理フィルター用線材において、芯部と芯部を取り囲む被覆部からなる2層構造とし、被覆部に、ポリアミド樹脂と、ポリエーテルエステルアミドブロックコポリマーまたはポリオキシアルキレン基含有ポリビニルアルコールとがブレンドしてなる樹脂組成物を配することにより、線材表面に高度な親水性を付与するとともに、実用的な機械的物性、耐久性を兼ね備え、ソイルリリース性に優れる水処理フィルターを提供することができる。
Smart Images

Figure 0007634254000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a wire made of a thermoplastic resin, which is used in a filter for filtering or separating water. [Background technology]
[0002] Conventionally, filters have been used to filter wastewater and separate water from solids. Metals and synthetic resins are used as materials for filters, but synthetic resin filters are advantageous in terms of corrosion resistance and light weight. Synthetic resin filters are used in various forms such as films or sheets with fine holes, woven fabrics, and nonwoven fabrics, but woven fabrics are superior in terms of filter strength, and woven fabrics using synthetic resin wires with large wire diameters are preferably used, especially when the water flow rate is high or the object to be filtered is highly abrasive. Various thermoplastic resins are used as materials for synthetic resin wires, but polyester and polyamide wires are advantageous in terms of mechanical properties, heat resistance, chemical resistance, and economy. Of these, polyester wires have the advantages of excellent dimensional stability in water, and polyamide wires have the advantages of excellent abrasion resistance. In addition, various types of dirt adhere to the wires during filtration, and such dirt must be removed, but polyamide wires have good soil release properties (ease of removing dirt) against water-based dirt because polyamide itself is hydrophilic. Patent Document 1 proposes a technique for disposing a cured product of epoxidized polyamide on the surface of a papermaking machine fabric, which is said to have antifouling properties that make it difficult for dirt to adhere and easy to clean off any dirt that does adhere. As a method for disposing a cured product of epoxidized polyamide on the surface of a fabric, a method for weaving a melt-spun fiber by melt-kneading a composition containing epoxidized polyamide with a polymer, and a method for impregnating, coating, or spraying a fabric with a solution of a composition containing epoxidized polyamide in water or various organic solvents are disclosed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent application 2002-68712 Summary of the Invention [Problem to be solved by the invention]
[0004] In the technique disclosed in the above-mentioned Patent Document 1, in the method of melt-kneading a composition containing an epoxidized polyamide with a polymer and weaving the melt-spun fibers, there are significant concerns about heat resistance and breakage during spinning. In addition, in the method of impregnating, coating or spraying a woven fabric with a composition containing an epoxidized polyamide as a solution in water or various organic solvents, there are concerns about the durability of the coating film containing the epoxidized polyamide adhered to the surface of the woven fabric due to friction during use in filtration.
[0005] An object of the present invention is to provide a wire constituting a water treatment filter, which has mechanical properties and durability required for practical use, and also has good soil release properties. [Means for solving the problem]
[0006] The present invention solves the above-mentioned problems by providing a continuous wire made of a thermoplastic resin, the cross section of which has a two-layer structure made of a core and a coating surrounding the core, The core is made of polyamide, The coating is made of polyamide. , polyether ester amide block copolymer The resin composition comprises a resin composition containing 60 to 97 mass % of polyamide, Polyetheresteramide block copolymer Contains 3 to 40 mass % of The gist of the invention is a wire for water treatment filters, characterized in that the wire has a wire diameter of 0.15 mm or more, a tensile strength of 5 N or more and 300 MPa or more in a wet state, and a tensile strength of 5 N or more and 300 MPa or more after dry heat treatment at 180°C for 30 minutes. The present invention also provides a continuous wire made of a thermoplastic resin, the cross section of which has a two-layer structure consisting of a core and a coating surrounding the core, The core is made of polyamide, the coating portion is composed of a resin composition containing polyamide and polyoxyalkylene group-containing polyvinyl alcohol, the resin composition containing 60 to 97% by mass of polyamide and 3 to 40% by mass of polyoxyalkylene group-containing polyvinyl alcohol; The gist of the invention is a wire for water treatment filters, characterized in that the wire has a wire diameter of 0.15 mm or more, a tensile strength of 5 N or more and 300 MPa or more in a wet state, and a tensile strength of 5 N or more and 300 MPa or more after dry heat treatment at 180°C for 30 minutes. Effect of the Invention
[0007] According to the present invention, the wire for water treatment filters has a two-layer structure consisting of a core and a coating surrounding the core, and the coating 、 Polyamide resin , polyether ester amide block copolymer or polyoxyalkylene group-containing polyvinyl alcohol By using a resin composition obtained by blending the above, it is possible to provide a water treatment filter that imparts a high degree of hydrophilicity to the wire surface, and that also has practical mechanical properties and durability, as well as excellent soil release properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention relates to a continuous wire constituting a water treatment filter, the continuous wire being made of a thermoplastic resin, and a cross section (transverse section) of the wire cut perpendicularly to its axial direction has a two-layer structure of a core and a coating surrounding the core. The number of cores is preferably one, but may be more than one. When there are more than one cores, the cores are each independent from one another and exist in the coating, forming a so-called sea-island structure in which the cores are islands and the coating is a sea. When there are more than one cores, the number of cores is preferably about 2 to 6.
[0009] The external cross-sectional shape of the wire is not particularly limited and may be circular, elliptical, polygonal, etc., but a circular cross section is preferred in terms of the mechanical properties and versatility that can be obtained.
[0010] The thermoplastic resin disposed in the core is polyamide from the viewpoints of mechanical properties and heat resistance.
[0011] The polyamide to be placed in the core is not particularly limited as long as it has an amide group in the molecule, and examples include polyamide 6, polyamide 66, polyamide 69, polyamide 46, polyamide 610, polyamide 1010, polyamide 11, polyamide 12, polyamide 6T, polyamide 9T, polyamide 10T, polymetaxylene adipamide, and copolymers or blends of these components.
[0012] The relative viscosity of the polyamide disposed in the core is preferably 2.5 or more, more preferably 3.0 or more, in order to obtain a practical strength and elongation. The relative viscosity of the polyamide is measured at a temperature of 25° C., at a concentration of 1 g / dl, using 96% sulfuric acid as a solvent.
[0016] The thermoplastic resin disposed in the core may contain other thermoplastic resins in small amounts within the range in which the object of the present invention is achieved. For example, is Polyester may be added to polyamide, and other thermoplastic resins include polyolefin, acrylic resin, vinyl acetate resin, vinyl chloride resin, vinylidene chloride resin, polytetrafluoroethylene, silicone resin, and polyurethane, which may be added alone or in combination.
[0017] In addition, various additives may be added to the thermoplastic resin disposed in the core, if desired. For example, dyes, pigments, dispersants, compatibilizers, spreaders, plasticizers, viscosity modifiers, flame retardants, lubricants, ultraviolet absorbers, infrared absorbing materials, microwave absorbing materials, light stabilizers, antioxidants, pH adjusters, antibacterial agents, preservatives, fillers, heat resistance agents, antistatic agents, conductive materials, thermally conductive materials, crystal nucleating agents, etc. may be added. In particular, by adding a compatibilizer to improve adhesion with the coating, it is preferable that the coating is less likely to peel off. As the compatibilizer, various block copolymers and graft copolymers can be used. Examples of block copolymers include block copolymers having blocks of polyester, polyether, polyamide, polystyrene, polyethylene, polypropylene, polybutadiene, polyacrylic acid, etc. Examples of graft copolymers include those using polyester, polyolefin, etc. as the main chain and vinyl polymer, maleic anhydride, glycidyl group, carboxylic acid group, etc. as the side chain. The amount of the compatibilizer added is preferably 20% by mass or less. If the amount added exceeds 20% by mass, the physical properties of the thermoplastic resin that is the base of the core are significantly impaired, which is not preferable.
[0018] In the wire of the present invention, the coating surrounding the thermoplastic resin of the core is polyamide. , polyether ester amide block copolymer or polyoxyalkylene group-containing polyvinyl alcohol The resin composition containing the above is disposed. The polyamide is not particularly limited as long as it has an amide group in the molecule, and examples thereof include polyamide 6, polyamide 66, polyamide 69, polyamide 46, polyamide 610, polyamide 1010, polyamide 11, polyamide 12, polyamide 6T, polyamide 9T, polyamide 10T, polymetaxylene adipamide, and copolymers or blends of these components. In order to obtain a practical strength and elongation, the relative viscosity of the polyamide is preferably 2.5 or more, and more preferably 3.0 or more. The relative viscosity of the polyamide resin is measured using 96% sulfuric acid as a solvent at a concentration of 1 g / dl and a temperature of 25°C.
[0020] The composition of the resin composition of the coating part is 60 to 97 mass % polyamide, Polyetheresteramide block copolymer or polyoxyalkylene group-containing polyvinyl alcohol The content of polyamide is 3 to 40 mass%. Alternatively, polyether ester amide block copolymers or polyoxyalkylene group-containing polyvinyl alcohols If the polyamide content is less than 3% by mass, the improvement in hydrophilicity of the coating is insufficient, and it is not possible to obtain a wire having good soil releasability, which is the objective of the present invention. Alternatively, polyether ester amide block copolymers or polyoxyalkylene group-containing polyvinyl alcohols If the content exceeds 40 mass %, the wire rod is unlikely to have a practical strength, and the productivity and handling properties of the wire rod are insufficient.
[0021] Other thermoplastic resins may be added to the resin composition of the coating portion in small amounts within the range in which the object of the present invention is achieved. For example, polyolefin, acrylic resin, vinyl acetate resin, polyester, vinyl chloride resin, vinylidene chloride resin, polytetrafluoroethylene, silicone resin, or polyurethane may be added alone or in combination.
[0022] The polyamide in the covering portion may contain various additives as desired. Examples of additives include the same additives as those added to the thermoplastic resin in the core portion described above.
[0023] The composite ratio (area ratio) of the core and coating of the wire of the present invention is preferably core:coating = 100:5-200, and may be appropriately selected taking into consideration the wire diameter and required mechanical properties, etc., but in order to satisfactorily combine improved physical properties derived from the core and hydrophilicity derived from the coating, it is more preferable that the core:coating = 100:10-100.
[0024] The wire of the present invention has a wire diameter of 0.15 mm or more. If the wire of the present invention is used to make a water treatment filter, the wire cannot withstand damage, wear, etc. caused by a high load during water treatment. The upper limit of the wire diameter is not particularly limited as long as the wire can be woven into a filter, but it is sufficient to have the wire diameter be about 1 mm.
[0025] In order to obtain resistance when used as a filter in water and resistance to processing heat such as heat setting in weaving using the wire, the wire has a tensile strength of 5N or more when a tensile test is performed in a wet state and after a dry heat treatment at 180°C for 30 minutes. If it is less than 5N, it is not suitable as a water treatment filter because it cannot withstand the tension applied during use. A more preferable tensile strength is 30N or more, and even more preferably 60N or more. The higher the tensile strength, the better, but an upper limit of about 1000N is considered sufficient. If the wire diameter is large, the strength (N) as a wire is high even if the strength (MPa) per unit cross-sectional area is low, but the strength per unit cross-sectional area (tensile strength when a tensile test is performed in a wet state and tensile strength after a dry heat treatment at 180°C for 30 minutes) is 300MPa or more, and more preferably 400MPa or more. In the present invention, the tensile test in a wet state means that a sample (wire) is placed in a container, the container is filled with tap water (20±2°C), the sample is immersed in water for 24 hours or more, and then the immersed sample is taken out of the water and immediately (within 1 minute) measured with a tensile tester, and a load is applied until it breaks. In addition, the tensile test after dry heat treatment at 180°C for 30 minutes means that a sample is placed in a hot air dryer heated to 180°C without load, taken out after 30 minutes, and stored under standard conditions (temperature 20±2°C, relative humidity 65±4%) for 24 hours or more, and then measured with a tensile tester and a load is applied until it breaks. The conditions for the tensile test are a grip interval of 250 mm, a tensile speed of 300 mm / min, and n=5. The average values of the maximum strength and the elongation at break are calculated, and the average values are the tensile strength and the elongation at break.
[0026] The wire of the present invention has a breaking elongation of 15 to 55%, more preferably 20 to 50%, when subjected to a tensile test in a wet state. If it is less than 15%, the wire becomes more brittle and has lower durability against bending fatigue, which is not preferable. If it exceeds 55%, the rigidity of the woven fabric decreases, resulting in insufficient filter precision, which is not preferable.
[0027] An example of a method for manufacturing a wire having a two-layer structure according to the present invention will be described. Resins or resin compositions (basically in pellet form) to be disposed in the core and coating are prepared, and the spinning temperature is set to about 260-290°C. The resins are melt-spun from a core-sheath composite spinneret using an extruder-type spinning device, and the spun product is cooled in a warm water bath at about 10-60°C to obtain an undrawn wire. This undrawn wire is stretched in a water bath at about 60-90°C (stretching ratio of about 2.5-4.5 times), and then stretched in a hot air atmosphere at 100-300°C (stretching ratio of about 1.1-2.5 times). This is followed by a relaxation heat treatment of about 2.5-30% in a hot air atmosphere at about 150-300°C to obtain a wire for water treatment filters according to the present invention. In order to adjust the handling property and surface properties, an oil agent for fibers may be applied online before or after stretching, or a coating film may be applied by coating or dipping in a post-process. In addition, post-processing such as plasma treatment may be performed to adjust the affinity with water and processability. EXAMPLES
[0028] The present invention will now be described in detail with reference to examples. The evaluation methods in the examples are as follows.
[0029] 1. Wire diameter measurement The wire diameter (mm) was calculated by averaging measurements taken at 20 points spaced 50 cm apart on the continuous wire.
[0030] 2. Tensile test (dry) Since continuous wire rods are usually wound up, the required amount was unwound and left at room temperature for 24 hours or more, after which a load was applied until the wire broke using a tensile tester, and the maximum strength and breaking elongation were measured. The conditions for the tensile test were a gripping distance of 250 mm, a pulling speed of 300 mm / min, and the average values measured with n=5 were taken as the maximum strength (N) and the breaking elongation (%).
[0031] 3. Tensile test (wet) Since continuous wire is usually wound, the required amount was unwound, the sample (wire) was placed in a container, the container was filled with tap water (20±2℃), and the sample was immersed in water for more than 24 hours, after which the immersed sample was taken out of the water and immediately (within 1 minute) measured with a tensile tester, a load was applied until it broke, and the maximum strength and breaking elongation were measured. The conditions for the tensile test were grip interval of 250 mm, tensile speed of 300 mm / min, and the average values measured with n=5 were taken as the maximum strength (N) and breaking elongation (%).
[0032] 4. Tensile test (after heat treatment) Since continuous wire is usually wound, the required amount was unwound and the sample was placed in a hot air dryer heated to 180°C without load, removed after 30 minutes and left for 24 hours or more under standard conditions (temperature 20±2°C, relative humidity 65±4%) before being measured with a tensile tester, where a load was applied until the sample broke, and the maximum strength and breaking elongation were measured. The conditions for the tensile test were grip interval 250mm, tensile speed 300mm / min, and the average values measured with n=5 were taken as the maximum strength (N) and breaking elongation (%).
[0033] 5. Abrasion resistance (flexion type abrasion test) The abrasion body was a 20 mm diameter metal rod with sandpaper #600 attached to the side, and the sample (wire) was brought into contact with this abrasion body at an angle of 90 degrees. A specified load was applied to one end of the sample, and the sample was rubbed back and forth with a stroke width of 120 mm and a stroke speed of 35 times / min, and the number of reciprocations until the sample broke was measured. Measurements were performed on n=4 samples, and the average of the obtained numbers was taken as the number of abrasion cycles for abrasion resistance. The specified load was determined based on the cross-sectional area (mm 2 For example, if the wire diameter is 0.45 mm, a load of 300 g is used.
[0034] 6. Pull-out test (soil release properties) A circular hole with a diameter of 4 mm was opened in a resin board (thickness 5 mm), and a continuous wire of sufficient length (about 20 cm) was conducted in the center of the hole so that at least about 15 cm of the continuous wire was protruding from the upper surface side of the resin board, and wood putty (manufactured by Cemedine Co., Ltd., product name "Wood Putty A Tamo White") was filled in, and the wood putty was left at room temperature to dry. Also, if the volume of the wood putty decreased due to drying while it was left, additional wood putty was filled in so that the upper and lower surfaces of the filled wood putty and the upper and lower surfaces of the resin board were almost the same. After the final additional filling, the resin plate was left for 2 days or more to allow the wood putty to dry thoroughly, and the wire sticking out from the bottom surface of the resin plate and the excess wood putty were cut off with a cutter along the bottom surface of the resin plate. The resin plate with the wire fixed with the wood putty was fixed horizontally to the bottom end of the tensile tester, while the wire sticking out at least 15 cm from the top surface of the resin plate was lifted vertically and fixed with a capstan chuck. When fixing with the capstan chuck, the chuck distance (distance from the top surface of the resin plate to the capstan chuck) of the wire (sample) was 100 mm, the tensile speed was 100 mm / min, n=5, and the maximum strength in the tensile test was measured, and the average value was taken as the pull-out strength (N). The smaller the pull-out strength value, the easier it is to remove firmly stuck dirt, and the soil release property was evaluated.
[0035] Example 1 In order to obtain a continuous wire having a composite cross section in which the core is surrounded by the coating, PA6 chips (polyamide 6, relative viscosity 3.5) were prepared as the resin composition for the core, and a chip blend of PA6 chips (polyamide 6, relative viscosity 3.5) and polyether ester amide block copolymer was prepared as the resin composition for the coating in a mass ratio of 95 / 5. Next, a normal extruder-type melt composite spinning device was used to melt spin the wire at a temperature of 270°C. The core and coating were weighed and spun so that the volume ratio of the core to the coating was 7 / 3. The spun wire was cooled in a warm water bath at 25°C to obtain an undrawn wire. This undrawn wire was drawn in a first stage without being wound up in a hot water bath at 80°C at a draw ratio of 3.0, then drawn in a second stage while passing through a heating zone at 175°C so that the total draw ratio became 4.8 (draw ratio of 1.6), and further passed through a heating zone at 175°C for 9% relaxation heat treatment to obtain a continuous wire with a two-layer structure. The obtained continuous wire had a diameter of 0.45 mm and an area ratio of the core part / coating part in the cross section was 7 / 3.
[0036] Example 2 In Example 1, the chip blend ratio of the resin composition of the coating part was polyamide 6 / Polyetheresteramide block copolymer Except for the above, the ratio of the core part to the coating part was 90 / 10, and a continuous wire was obtained in the same manner as in Example 1. The obtained continuous wire had a diameter of 0.45 mm and an area ratio of the core part to the coating part in the cross section of 7 / 3.
[0037] Example 3 In Example 2, Instead of polyether ester amide block copolymer, Except for using polyoxyalkylene group-containing polyvinyl alcohol, a continuous wire was obtained in the same manner as in Example 2. The obtained continuous wire had a diameter of 0.45 mm and an area ratio of the core part / coating part in the cross section of 7 / 3.
[0038] Comparative Example 1 Using only the PA6 chip used in Example 1, a normal extruder-type melt spinning device was used to melt-spin at a temperature of 270°C. The spun wire was cooled in a hot water bath at 25°C to obtain an undrawn wire. Without winding, this undrawn wire was subjected to a first-stage drawing at a draw ratio of 3.0 times in a hot water bath at 80°C, and then to a second-stage drawing (draw ratio of 1.6 times) while passing through a heating zone at 175°C so that the total draw ratio became 4.8 times, and then to a 9% relaxation heat treatment by passing through a heating zone at 175°C to obtain a single-phase continuous wire made of only polyamide. The obtained continuous wire had a diameter of 0.45 mm.
[0039] The physical properties of the obtained continuous wires of Examples 1 to 3 and Comparative Example 1 are shown in Table 1.
[0040] [Table 1]
[0041] The continuous wires of Examples 1 to 3 have practically sufficient tensile strength and tensile strength in both dry and wet conditions, as compared with the continuous wire of Comparative Example 1 made only of polyamide, and also have good abrasion resistance equivalent to that of Comparative Example 1. Furthermore, the pull-out strength of Examples 1 to 3 is smaller than that of Comparative Example 1, and the soil release property is improved. This is considered to be due to the improved hydrophilicity of the wire surface in the continuous wire of the Examples, and the improved adhesion to the wood putty that is attached as dirt. From these measurement results, the wires of Examples 1 to 3 can provide a water treatment filter that has the mechanical properties and durability required for practical use, while improving the hydrophilicity of the wire surface, thereby improving the processability and soil release property.
Claims
1. A continuous wire made of a thermoplastic resin, the cross section of which has a two-layer structure consisting of a core and a coating surrounding the core, The core is made of polyamide, the coating portion is composed of a resin composition containing a polyamide and a polyetheresteramide block copolymer, the resin composition containing 60 to 97% by mass of polyamide and 3 to 40% by mass of the polyetheresteramide block copolymer; The wire for water treatment filters has a wire diameter of 0.15 mm or more, a tensile strength of 5 N or more and 300 MPa or more in a wet state, and a tensile strength of 5 N or more and 300 MPa or more after dry heat treatment at 180°C for 30 minutes.
2. A continuous wire made of a thermoplastic resin, the cross section of which has a two-layer structure consisting of a core and a coating surrounding the core, The core is made of polyamide, the coating portion is composed of a resin composition containing polyamide and polyoxyalkylene group-containing polyvinyl alcohol, the resin composition containing 60 to 97% by mass of polyamide and 3 to 40% by mass of polyoxyalkylene group-containing polyvinyl alcohol; The wire for water treatment filters has a wire diameter of 0.15 mm or more, a tensile strength of 5 N or more and 300 MPa or more in a wet state, and a tensile strength of 5 N or more and 300 MPa or more after dry heat treatment at 180°C for 30 minutes.
Citation Information
Patent Citations
Method for supplying high concentration ozone gas and its apparatus
JP2002068712A
Polyamide monofilament and fishing gut
JP2003286615A
Core-sheath conjugated polyamide monofilament
JP2004308020A
Filter cloth
JP2005169177A
Composite fiber
WO2006025610A1